2018
DOI: 10.24052/jbrmr/v12is04/art-22
|View full text |Cite
|
Sign up to set email alerts
|

Environmental disclosure in the annual reports of the Russian retailers

Abstract: The implementation of extended business environmental liability is an essential condition for sustainable development of the Russian economy, including in retail. Retailers' interest in environmental issues is related both to the enhancement of public control and to the possibility of acquiring additional competitive advantages and economic benefits. Effective environmental management aimed at achieving benefits and advantages involves disclosing of environmental information to the public. The present study fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…14 A large number of studies have tried to analyse corporate environmental disclosure (CED) practices in the annual reports. [15][16][17][18][19][20][21][22] Most of these studies found that corporate environmental disclosures have increased over time. However, these disclosures were found to be mostly descriptive or narrative in nature.…”
Section: Theoretical Background and Objectives Of The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…14 A large number of studies have tried to analyse corporate environmental disclosure (CED) practices in the annual reports. [15][16][17][18][19][20][21][22] Most of these studies found that corporate environmental disclosures have increased over time. However, these disclosures were found to be mostly descriptive or narrative in nature.…”
Section: Theoretical Background and Objectives Of The Present Studymentioning
confidence: 99%
“…There were 30 companies in oil drilling & exploration and refinery sectors listed on National Stock Exchange (NSE) and Bombay Stock Exchange (BSE). Twenty-two (22) companies were common on both the exchanges, 4 companies were listed only on BSE and 4 companies were not traded. Therefore, 26 out of 30 listed companies were taken as sample in this study.…”
Section: Sample Selectionmentioning
confidence: 99%